A new Amazonian species of Allobates Zimmermann & Zimmermann, 1988 (Aromobatidae) with a trilled advertisement call - Silva, Leandro A. (2022)
Background: Currently, 58 species are assigned to the genus Allobates, with 70% of its diversity described just in the last two decades, with many additional species likely unnamed. The continuous description of these new species represents a fundamental step for resolving the taxonomy and ensuring the future conservation of the genus. Methods: Using molecular, acoustic, and morphological evidences, we describe a new species of Allobates from Teles Pires River region, southern Amazonia, and provide accounts on the population of A. tapajos found sympatrically with the new species. Results: The new species is distinguished from its congeners by the coloration of thighs, venter, dorsum, and dark lateral stripe. It has four types of calls, with advertisement calls formed by relatively long trills with a mean duration of 2.29 s ± 0.65, mean of 39.93 notes ± 11.18 emitted at a mean rate of 17.49 ± 0.68 notes per second, and mean dominant frequency of 5,717 Hz ± 220.81. The genetic distance between the new species and its congeners in a fragment of the 16S mitochondrial fragment ranged between 13.2% (A. carajas) to 21.3% (A. niputidea). The sympatric Allobates population fits its morphology and acoustic with the nominal A. tapajos, but presents a relatively high genetic distance of nearly 6.5%, raising questions on the current taxonomy of this species.